CO2 storage in heterogeneous aquifer: A study on the effect of temperature and mineral precipitation - Raza, A.; Gholami, R.; Rezaee, R.; Bing, C.; Ramasamy, Nagarajan; Hamid, M. (2017)
© Published under licence by IOP Publishing Ltd. CO2 storage in suitable geologic media has been recognized as a major strategy taken to have a carbon free environment. This practice can be done in depleted reservoirs as well as brine aquifers where sufficient storage capacity is available to hold carbon dioxide for thousands of years. Storage in an aquifer is often achieved through four trapping mechanisms, among which capillary trapping is a rapid and effective phenomenon. Although, there have been studies pointing out the relationships of different storage related factors with capillary trapping, more studies are still required to recognize other parameters linked to this effective trapping mechanism. The aim of this paper is to evaluate the effect of temperature and mineral precipitation on trapping mechanisms of heterogeneous aquifer. A dynamic numerical simulation was run by the commercial reservoir simulator Eclipse300 to simulate 30 years of CO 2 injection. A synthetic but realistic model of a geologic formation was considered to evaluate the efficiency of trapping mechanisms under different temperature and mineral precipitation conditions. The results obtained indicated that trapping mechanisms are affected by both temperature and mineral precipitation in a short and long terms - temperature is indirectly affecting the trapping ability regardless of the precipitation effect. However, precipitation have a severe impact on injectivity as well as trapping mechanisms in the long term. Although some practical conclusions were drawn, the results obtained and presented in this study may need experimental verification before taking into serious consideration.